Charles H. Rogers family papers - Rogers, Charles H.
Correspondence, military orders and passes, notes, calling cards, and a photograph. Includes correspondence from Ulysses S. Grant and his family relating chiefly to family matters and social engagements during the Grant family's residency in the White House (1869-1877) and their world tour (1877-1879). Other correspondents include Orville Elias Babcock, Adam Badeau, Julia Sands Bryant, William Cullen Bryant, John A. Rawlins, J. C. Smith, and E. B. Washburne. Smith's correspondence details the activities of the 96th Illinois Infantry Regiment during his Civil War service in that regiment.
Financier.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Babcock, Orville Elias, -- 1835-1884 -- Correspondence; Badeau, Adam, -- 1831-1895 -- Correspondence; Bryant, Julia Sands, -- 1831-1907 -- Correspondence; Bryant, William Cullen, -- 1794-1878 -- Correspondence; Grant, Ulysses S. -- 1822-1885 -- Correspondence; Grant, Ulysses S. -- 1822-1885 -- Travel; Rawlins, John A. -- 1831-1869 -- Correspondence; Smith, J. C. -- Correspondence; Washburne, E. B. -- 1816-1887 -- Correspondence; Grant family; Grant family -- Correspondence; United States. -- Army. -- Illinois Infantry Regiment, 96th (1862-1865); White House (Washington, D.C.); United States -- History -- Civil War, 1861-1865.; Washington (D.C.) -- Social life and customs; Financiers